A Colorimetric Method for Quantifying Cis and Trans Alkenes Using an Indicator Displacement Assay. Issue 25 (13th May 2021) - Valenzuela, Stephanie A.; Crory, Hannah S. N.; Yao, Chao‐Yi; Howard, James R.; Saucedo, Gabriel; de Silva, A. Prasanna; Anslyn, Eric V.
Abstract: A colorimetric indicator displacement assay (IDA) amenable to high‐throughput experimentation was developed to determine the percentage of cis and trans alkenes. Using 96‐well plates two steps are performed: a reaction plate for dihydroxylation of the alkenes followed by an IDA screening plate consisting of an indicator and a boronic acid. The dihydroxylation generates either erythro or threo vicinal diols from cis or trans alkenes, depending upon their syn ‐ or anti ‐addition mechanisms. Threo diols preferentially associate with the boronic acid due to the creation of more stable boronate esters, thus displacing the indicator to a greater extent. The generality of the protocol was demonstrated using seven sets of cis and trans alkenes. Blind mixtures of cis and trans alkenes were made, resulting in an average error of ±2 % in the percentage of cis or trans alkenes, and implementing E2 and Wittig reactions gave errors of ±3 %. Furthermore, we developed variants of the IDA for which the color may be tuned to optimize the response for the human eye. Abstract : A high‐throughput method was developed using a colorimetric indicator displacement assay (IDA) to quantify the alkene stereochemistry present within mixtures to an accuracy of 2–3 %. Within a series of 96‐well plates, alkenes were dihydroxylated and the resulting diols were subjected to an IDA with an indicator and a boronic acid to determine the amount of threo and/or erythro vicinal diols present.